Analisis Wacana Kritis Teun A Van Dijk dalam Pernyataan Menteri Agama tentang Aturan Pengeras Suara Masjid - Durri Yatul Lumah; Rr. Sulistyawati (Peneliti.net, 2022)
This Study Aim to explain the discourse built by the minister of religion in his statement regarding the rules of mosque loudspeakers through the point of view of A Van Dijk Critical Discourse Analysis. This research is a qualititaive research with content analysis method. This Source of the data comes from Yaqut Cholil's speech during an interview with journalist. Data collection was carried out by analyzing the discourse bulit by Yaqut Cholil's through his statement regarding the rules of loudspeakers for mosques/musalas. The results of teh study found that the microstructural elements were the most common elements which contained semantic, syntactic, stylisctic, and rhetorical aspect. The macro structure element which contains the thematic aspect shows the theme or topic that can be inferred from the overall content of Yaqut Cholil's discourse, and the superstructure element which contains the scematic or plot aspect. The characteristic of critical discourse analysis in the statement of the minister of religion Yaqut Cholil regarding mosque/musala loudspeakers indicate that Yaqut Cholil's discourse fulfills the characterictics of critical discourse analysis which contains action, context, history, power, and ideology